FAKTOR-FAKTOR INTERNAL DAN EKSTERNAL YANG MEMPENGARUHI KEBIJAKAN PERDAGANGAN AMERIKA SERIKAT TERHADAP HUAWEI (Periode 2018-2019) - Erikson (2022)
This thesis aims to explain a series of trade policies issued by the United States government, as well as to find out what are the factors both internal and external to the telecommunications technology company from China, Huawei. The research is based on the existence of a series of policies that create dynamics in the relationship between the two parties and the continuity of cooperation with one another. The dynamics that occur create a political escalation, which is because the US and Huawei issues occur in the midst of the chaotic US trade war with Huawei's home country, China. This can certainly be seen as one of the factors influencing US policy towards Huawei, in addition to a series of accusations from the US regarding the theft of intellectual property and activities that threaten national security by Huawei. Tensions between the US and China have brought Huawei into the vortex of a trade war conflict. The analysis is carried out by using qualitative research methods that seek to describe a pattern through interpretation of the sources and data collected.